Transplante combinado fígado-rim : experiência de um hospital universitário brasileiro - Veras, Francisca Jovita de Oliveira (2014)
Background: Combined liver–kidney transplant is a routine procedure in many transplant centers. The increase in its number coincided with the introduction in 2002 of the MELD (Model for End-stage Liver Disease) score for allocation of livers, prioritizing patients with renal dysfunction. Aim: To analyze the experience with combined liver-kidney transplantation in a liver transplant center in Brazil. Method: A retrospective review was conducted. All transplants were performed using grafts from deceased donors. Results: Sixteen combined liver-kidney transplantations were performed in the same period, which corresponds to 2.7% and 2.5% of the kidney and liver transplants, respectively. Fourteen patients were male (87.5 %) and two were female (12.5%). The average patients and donors age was 57.3±9.1 and 32.7±13.1, respectively. The MELD score mean was 23.6±3.67. The main cause of liver dysfunction were chronic hepatitis C virus (n=9). As for renal dysfunction, diabetic nephropathy (n=4) was the most frequent. There were six deaths, two of them by severe dysfunction of the liver graft and four by infectious causes. The 1, 3 and 5 years survival rate in patients undergoing liver-kidney transplantations was 68.8%, 57.3% and 57.3%, respectively. Conclusion: The survival rates achieved in this series are considered satisfactory and show that this procedure has an acceptable morbidity and survival.